O Glust I Glust - Owen, Llwyd (Y Lolfa, 2022)
A detective novel by a prize winning author. The time has come for revenge... revenge for what happened many years ago. There is a killer at large, one who is now ready to seek revenge. One dark night, he strikes. He claims his first victim, but not the last.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books